2008
DOI: 10.1080/09645290802500263
|View full text |Cite
|
Sign up to set email alerts
|

Education policy, growth and welfare

Abstract: This paper studies the general equilibrium implications of two types of education policy in an overlapping generations model. We examine vouchers, which augment inherited private education spending, and public investment on economy-wide human capital, that provides externalities to individual human capital accumulation.The government determines jointly the tax rate and the allocation of tax revenues among the two types of education policy. The optimal division of public spending between the education policy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Universities should teach students not only the professional knowledge and skills, but also the principles of social equity and humanism, engaging them in social and volunteer activities to benefit all sectors of society. Benos (2010) confirmed that human capital accumulation has been identified as a fundamental source of long-run growth and income inequality in modern economies. In some countries there is a significant public intervention in education, while in others there is extensive private financing of the education sector (e.g.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Universities should teach students not only the professional knowledge and skills, but also the principles of social equity and humanism, engaging them in social and volunteer activities to benefit all sectors of society. Benos (2010) confirmed that human capital accumulation has been identified as a fundamental source of long-run growth and income inequality in modern economies. In some countries there is a significant public intervention in education, while in others there is extensive private financing of the education sector (e.g.…”
Section: Introductionmentioning
confidence: 67%
“…For another thing, higher education programs allow a person to get professional competencies needed to effectively build a future career. According to the editorial board of the magazine "Academy of Management Learning & Education" (Benos, 2010), http://dx.doi.org/10.15405/epsbs.2017.01.94 eISSN: 2357-1330 responsibility of the Conference Organization Committee education needs to the transition to a new paradigm based on human well-being. It is noted that higher education gives an individual a healthy understanding of humanistic culture.…”
Section: Introductionmentioning
confidence: 99%
“…This indicator reflects the quality of the learning environment and the incentives for students to attend courses, pay attention, acquire knowledge, and improve their skills. This ratio varied slightly over the last decade and improved slightly, settling at under 19 students per teacher in 2007. Still, in 2005, Tunisia had a much higher student to teacher ratio (19.4:1) compared to those for the LMI countries (17.5:1), the OECD average (14:1), and the world (15:1).…”
Section: Internal Efficiencymentioning
confidence: 79%
“…It turned out that the developed economies or the economies of the developing countries have more efficient systems of education, science and research. The same holds for the economic welfare, which is inconceivable without continuous accumulation of knowledge arising from the education and scientific system (Benos, 2010).…”
Section: Economic Implications Of Education In Southeast Europementioning
confidence: 93%